2016
DOI: 10.1177/1077546316660029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the rheological parameters of a hydro-viscoelastic system consisting of a viscoelastic plate, viscous fluid and rigid wall on the frequency response of this system

Abstract: In this paper the forced vibration of a hydro-viscoelastic system consisting of a viscoelastic plate, compressible viscous fluid and rigid wall is considered. The focus is on the investigation of the influence of the rheological parameters of the plate material and the viscosity of the fluid on the frequency response of this system. The constitutive relations for the plate material are given through the fractional-exponential operators, and the exact equations of the visco-elastodynamics in the plane-strain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The present work can also be considered as further development of the second author's work from the last decade dealing with the forced vibration of single-layer purely elastic or viscoelastic plates in contact with a compressible viscous fluid (see, for example, the works [5][6][7]). A review of these works can be found in the paper by Akbarov [3].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The present work can also be considered as further development of the second author's work from the last decade dealing with the forced vibration of single-layer purely elastic or viscoelastic plates in contact with a compressible viscous fluid (see, for example, the works [5][6][7]). A review of these works can be found in the paper by Akbarov [3].…”
Section: Introductionmentioning
confidence: 95%
“…Using the expressions in ( 37), ( 40), ( 8), (7), and ( 6), the following expressions are obtained for the quantities related to the fluid flow:…”
Section: Determination Of the Fourier Transforms Of The Quantities Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…Akbarov, M.I. Ismailov where the motion of the plate is described by three‐dimensional linearized equations of wave propagation in elastic bodies with initial stresses, and the liquid flow is described with linearized Navier‐Stokes equations. The problems of non‐linear oscillations of plates moving in an ideal incompressible liquid were studied in works [].…”
Section: Introductionmentioning
confidence: 99%